Combat Time in International Male Judo Competitions: A Systematic Review and Meta-Analysis - Barreto, Lindsei Brabec Mota; Santos, Marco A.; Fernandes Da Costa, Lucas O.; Valenzuela, Diego; Martins, Felipe J.; Slimani, Maamer; Bragazzi, Nicola L.; Miarka, Bianca; Brito, Ciro José (Frontiers in Psychology, 2022)
This study aimed to synthesize literature data on male judo combat time in international competitions between 2010 and 2019. The search was carried out from May 8th to June 11th, 2021, in electronic databases using the following keywords: (“technical-tactical” OR “time motion” OR “combat time”) AND (“judo” OR “combat sports” OR “martial arts”). After the selection process, 8 articles were included in the systematic review and 7 in the meta-analysis. These studies analyzed 2,562 international male judo combats over the years 2010 to 2019. We observed that the average male judo combat time changed (2010=202.8; 2011-2012=304.8; 2016=237.4; 2018-2019=189.8 seconds) after each rule change (2010, 2013, 2017 and 2018). There was a significant difference between combats that ended up to the regular time and those that needed overtime (Golden Score: 2013=3% vs. 2018-2019=21%; p=0.03). There were differences between 60kg (p≤0.019) and +100kg (p≤0.04) categories and the others in 2011-2012. However, no significant difference was found between the combat time by weight division after the 2017 rule changes, although there are still differences in relation to the end of the combats (p<0.001). There were significant changes in the male judo combat time with each rule change (2010, 2013, 2017 and 2018), and the data from the included studies point to a trend of homogeneity in the combat time spent between the weight divisions over the years, and an increase in the occurrence of Golden Score. More studies need to be carried out to identify the new temporal behaviors of athletes.